Ordinary hydrophobicity of mesoporous faujasites boosting the catalytic ketalization of glycerol with acetone - Pazin, Leonardo H. [UNESP]; Zapelini, Iago W. [UNESP]; Santagneli, Silvia H. [UNESP]; Sad, María Eugenia; Padró, Cristina; Martins, Leandro [UNESP] (Elsevier, 2024)
A series of faujasite zeolites were used in the glycerol ketalization reaction with acetone. This zeolitic structure is widely explored in cracking reactions and has known mesoporosity and hydrophobicity, resulting from the treatments conducted to remove aluminum atoms from the framework and produce a stabilized structure containing different Si/Al ratios. Such properties, in combination with the typical acidity of zeolites, are extremely suitable for driving the ketalization reaction, a two-phase reaction that involves bulky compounds (compared to the size of the zeolitic pores) and that is reversible with the formation of water as a byproduct. The presence of mesopores in the zeolites was confirmed from the pore size distribution using nitrogen physisorption isotherms. Hydrophobicity was confirmed indirectly by thermogravimetry, measuring the amount of water adsorbed and the water desorption temperature. The contact angle of zeolites with glycerol showed only a slight increase with the increase in the Si/Al ratio due to a rise in SiOH groups, defects that naturally arose from removing aluminum atoms. Despite the high concentration of structural hydrophilic SiOH groups, the accessibility and hydrophobicity of isolated Brønsted acid sites (up to Si/Al = 250) inside the zeolitic pores were important to guarantee an improved performance in the reaction.
Keywords: reversible reactions; SiOH defects; two-phase reaction; USY zeolites